Corporate governance in Malaysia: framework, challenges & the way forward - Wong, Ying Jun (2025)
This paper seeks to explore the development of corporate governance in Malaysia and to provide an overview of the corporate governance framework in Malaysia in light of recent efforts to boost corporate governance amongst micro, small and enterprises in Malaysia, with a view of identifying the effectiveness and challenges of these reforms and providing recommendations to strengthen corporate governance to achieve the ultimate goals of sustainable business growth, corporate accountability, improved shareholder value and stakeholder interest protection.